Cover Image, Volume 85, Issue 3. Issue 3 (March 2017) - Lensink, Marc F.; Velankar, Sameer; Wodak, Shoshana J.
Abstract : The cover image, by Marc F. Lensink et al., is based on the Article Modeling protein‐protein and protein‐peptide complexes: CAPRI 6th edition, DOI:10.1002/prot.25215 .